Environmental variability and the evolution of the glucocorticoid receptor (Nr3c1) in African starlings. (8th August 2016) - Hofmeister, Natalie R.; Rubenstein, Dustin R.
Abstract: One of the primary ways that organisms cope with environmental change is through regulation of the hypothalamo–pituitary–adrenal (HPA) axis, the neuroendocrine system that controls reactions to stress. Variation in genes regulating the HPA axis – particularly the glucocorticoid receptor – may facilitate adaptation to changing climatic conditions by altering expression. Here we examine signatures of selection on the glucocorticoid receptor gene ( Nr3c1 ) in African starlings that inhabit a range of environments, including those with variable climatic conditions. To investigate potential adaptive mechanisms underlying the vertebrate stress response, we sequence the Nr3c1 gene in 27 species of African starlings. Although we find some evidence of positive selection, substitution rate is negatively correlated with variance in precipitation. This suggests climatic cycling in sub‐Saharan Africa may have resulted in lower substitution rates to maintain a successful coping strategy. When environmental conditions fluctuate rapidly, variation in the strength of purifying selection can explain evolutionary rate variation.